Sacred and profane mortal and venial comic stories - Green, Justin 1945- (Last Gasp, 2022)
Black and white jumbo-sized comic from the legendary cartoonist Justin Green. The oversize pages allow the reader to fully appreciate Green's artwork. Includes stories with Binky Brown and Rowdy Noody, as well as the baseball classic "Right Field" (Read it and weep). The center spread is the masterpiece 'The Gates of Purgatory.' Also printed in large format is the complete five-part serial of "We Fellow Traveleers" where Justin and his brother and alter-ego Babyface find themselves trapped in the Saw-Church of Profanity. Originally published in 1976, this underground classic is now available!--amazon.com
Cover title
Keywords: Cartoonists / United States / Comic books, strips, etc; Underground comic books, strips, etc; Bandes dessinées underground; underground comics; Underground comics; Comic